1999
DOI: 10.1103/physrevlett.83.5015
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Observation of Ultrahigh Intensity Laser-Produced Electron Jets Propagating through Transparent Solid Targets

Abstract: We report on shadowgraphic measurements showing the first space-and time-resolved snapshots of ultraintense laser pulse-generated fast electrons propagating through a solid target. A remarkable result is the formation of highly collimated jets (,20-mm) traveling at the velocity of light and extending up to 1 mm. This feature clearly indicates a magnetically assisted regime of electron transport, of critical interest for the fast ignitor scheme. Along with these jets, we detect a slower (ഠc͞2) and broader (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(88 citation statements)
references
References 21 publications
7
81
0
Order By: Relevance
“…The latter experiments have been performed using green light of approximately the same pulse duration with laser intensities up to 4 × 10 18 W/cm 2 and 10 19 W/cm 2 , correspondingly. However, the penetration depth of hot electrons in [24] was more than two orders of magnitude longer than in [25]. Two possible disparate scenarios may explain these controversies in high-energy electron and ion generation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter experiments have been performed using green light of approximately the same pulse duration with laser intensities up to 4 × 10 18 W/cm 2 and 10 19 W/cm 2 , correspondingly. However, the penetration depth of hot electrons in [24] was more than two orders of magnitude longer than in [25]. Two possible disparate scenarios may explain these controversies in high-energy electron and ion generation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in [27], which models the transport of fast electrons generated by a 20-J laser, it was shown that only 0.6 J are required to ionize a target of 250-µm thickness. Note that the experiment in [24] was performed with an order of magnitude higher laser energy (and so larger prepulse energy) than the experiment in [25], which displayed a dramatic difference in the hot-electron penetration depths. The aim here is to see how both underdense preplasma scale length and solid dense plasma thickness determine the efficiency of ion generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…resolving studies on electron propagation in condensed matter employed laser-based spectroscopic techniques to reveal ballistic currents and drift motion of charge carriers [6][7][8][9] .…”
mentioning
confidence: 99%
“…Additionally, electromagnetic and electrostatic instabilities can arise, e.g. the Weibel instability [59][60][61][62][63] and electron filaments can be generated. When the electrons reach the rear side of the target only the fastest electrons (precursor electrons) can escape since a potential will be build up which hinder the electrons to escape.…”
Section: Target Normal Sheath Accelerationmentioning
confidence: 99%